E-democracy and knowledge: A multicriteria framework for the new democratic era - José María Moreno-Jiménez; Wolfgang Polasek (Institute for Advanced Studies (IHS), 2003)
This paper analyses a new framework for decision-making in e-democracies that exploits the power of Internet based public knowledge, which is called briefly e-cognocracy. This is not a procedure to improve technical aspects using the Internet (e.g. e-voting); it is rather a procedure to add a new quality to the democratic system by using the network. This proposed system of e-cognocracy would allow those who are interested to solve highly complex problems by participatory decision-making. Furthermore, we suggest the multicriteria framework for the modelling and resolution of such complex problems. Similarly, using the analytic hierarchy process (AHP) approach, we propose decisional (analytic and informatic) tools for searching the knowledge - relevant for the decision-making process. This knowledge of patterns of behaviour, trends, opportunities, decisions and stylised facts will be the starting point of a consensus-reaching process, which is aimed to effectively solve problems of high complexity of the Internet society.
Keywords: H10; 330; e-democracy; knowledge society; e-cognocracy; multicriteria; AHP criterion; consensus; Wahl; Abstimmungsregel; Ökonomische Theorie der Demokratie; Internet; AHP-Verfahren